Portrait of Capital Accounting Practiced by Students of Sharia Accounting Department From Gorontalo Ethnic - Thalib, Mohamad Anwar (Etihad: Journal of Islamic Banking and Finance, 2022)
This study aims to reveal the values of local wisdom from the way students majoring in Islamic accounting from the Gorontalo tribe practice capital accounting. This study uses an Islamic paradigm with an Islamic ethnomethodology approach. There are five data analysis stages: charity (amal), knowledge (ilmu), faith (iman), information revelation (informasi wahyu), and good deeds (ihsan). The results showed that before receiving the scholarship, the initial capital to finance college was obtained by students from both their parents and their families. The practice of capital accounting is conditional on the value of local wisdom in the form of responsibility. This value is one of the advice the elders often express through lumadu "delo sipati lo malu'o tiloliyo kulu-kulu wala'iyo modudu'o which has a meaning in the form of a feeling of family responsibility".Penelitian ini bertujuan untuk mengungkap nilai-nilai kearifan lokal dari cara mahasiswa jurusan akuntansi syariah yang berasal dari suku Gorontalo mempraktikkan akuntansi modal. Penelitian ini menggunakan paradigma Islam dengan pendekatan etnometodologi Islam. Terdapat lima tahapan analisis data yaitu amal, ilmu, iman, informasi wahyu, dan ihsan. Hasil penelitian menunjukkan bahwa sebelum menerima beasiswa maka modal awal untuk membiayai kuliah diperoleh oleh mahasiswa dari kedua orang tua dan keluarga mereka. Praktik akuntansi modal tersebut syarat dengan nilai kearifan lokal berupa tanggung jawab. Nilai ini merupakan salah satu nasihat yang sering diungkapkan oleh tua-tua melalui lumadu “delo sipati lo malu’o tiloliyo kulu-kulu wala’iyo modudu’o yang memiliki makna berupa perasaan tanggung jawab keluarga”.